The Impact of Financial Literacy on Investment Decisions: With Special Reference to Undergraduates in Western Province, Sri Lanka - T, Kumari D.A. (Asian Journal of Contemporary Education, 2020)
Financial literacy is defined as the possession of knowledge and skills that enable informed and effective money management. Financial literacy is enhancing the financial developments and economic growth of the country. In the face of these developments, it is important to assess if the younger generation, especially undergraduates who are seen as the future investors, movers and transformers of the economy, have the necessary knowledge of financial concepts. This study examines the impact of financial literacy on investing decisions among undergraduates in the western province in Sri Lanka. A total of 200 students from 4 government universities in the western province of Sri Lanka participated in this study. The present study employed a few determinants to assesses financial literacy as students’ knowledge about financial products, Accessing financial products, money management, knowledge about financial investment option, and financial skills. The study focused to examine, how a student's level of financial literacy influences his/her financial opinions, decisions and practices. The findings revealed that financial literacy positively and significantly influenced on the undergraduates’ investment decisions. Further, when it focused on the dimensions of financial literacy, the most significant dimension was financial skills. The knowledge about the financial product is identified as the least significant dimension on investment decision of the undergraduates. Finally, the researcher provides some suggestions for financial institutions and policy decision-makers to develop financial literacy level by promoting financial knowledge for enhancing the investment decision making power among the young generation in Sri Lanka.